2001
DOI: 10.1002/chir.10024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, resolution, and investigation of the rotational interconversion process of atropisomeric 1,n‐diaza[n]paracyclophanes using cyclodextrin‐mediated capillary zone electrophoresis

Abstract: A number of variously monosubstituted 1,n-diaza[n]paracyclophanes (n = 10-12), which show planar chirality and atropisomerism due to hindered rotation about single bonds, were synthesized via a classical route to analyze their stereodynamic properties. Racemic analytes with 10- and 11-membered bridges were resolved by capillary zone electrophoresis (CZE) in acidic phosphate buffers (pH 2.5-4.5) employing permethylated beta- and gamma-cyclodextrin as chiral additives. Moreover, cyclodextrin mediated CZE was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Research by Kanomata has similarly reported the synthesis of enantiomeric cyclophanes with 10 and 11 carbons isolable at room temperature [13]. Quantitatively similar results have also been found with 1,n-dioxa[n]paracyclophanes and 1,n-diaza[n]paracyclophanes [14,15]. Whether similar tether lengths will yield comparably isolable atropisomers at room temperature for diarylethyl cyclophanes remains unknown and is the point of this investigation.…”
Section: Introductionsupporting
confidence: 52%
“…Research by Kanomata has similarly reported the synthesis of enantiomeric cyclophanes with 10 and 11 carbons isolable at room temperature [13]. Quantitatively similar results have also been found with 1,n-dioxa[n]paracyclophanes and 1,n-diaza[n]paracyclophanes [14,15]. Whether similar tether lengths will yield comparably isolable atropisomers at room temperature for diarylethyl cyclophanes remains unknown and is the point of this investigation.…”
Section: Introductionsupporting
confidence: 52%
“…In continuation of these studies, Scharwächter et al [150] investigated a number of atropisomeric 1,n-diaza [n]paracyclophanes 32 (n 5 10-12; X 5 H, CH 3 , CF 3 , Cl, Br, NO 2 , and F). Enantiomerization barriers between 111.2 and 126.1 kJ/mol, which depend on the bulkiness of the substituent X (NO 2 )CF 3 4Br4Cl4CH 3 EF), could be determined demonstrating the great potential of sfCE.…”
Section: Atropisomersmentioning
confidence: 98%
“…19). 44 They obtained pH-dependent energy barriers ranging from 113 to 126 kJ mol 21 that were dramatically reduced by 6-8 kJ mol 21 in the presence of cyclodextrin derivatives. Schurig and coworkers applied the principles of stopped-flow chromatography to gas chromatography albeit with significantly lower accuracy when the measurements required very high temperatures.…”
Section: Chromatographic and Electrophoretic Stopped-flow Analysismentioning
confidence: 99%